MEMBANGUN POLITIK KRIMINAL PADA PERTAMBANGAN BATUBARA YANG MENYEJAHTERAKAN MASYARAKAT MELALUI SARANA NON-PENAL - Firmansyah, Arif; Suhardiman, Euis D. (Lampung University, 2015)
In Article 33 paragraph (3) of the Constitution of 1945, states earth water and natural resources contained therein controlled by the state and used for the welfare of the people. The realization of such mastery by delegating the authority to manage the natural resources of the state to the company is to provide state Mining Permit or Special Mining Permit. In protecting and overseeing the company that is engaged in coal mining government passed Law Number 4 of 2009 on Mineral and Coal Mining. In Article 162 of Law Number 4 of 2009 states that every person who impede or interfere mining activities from business license holders of mining and business permit of the mining specifically penalized by fines or imprisonment. The article shows a process of criminalization an action (criminal policy), which aim to protect the companies that already have a Mining Permit, but the criminal policy is contrary to the purpose of the criminal policy is an effort for the welfare of society and policies the protection of society, the existence of Article 162 of Law Minerals coal and coal mining communities can impede convicted. In the case of the counteraction form caused they want to protect the environment or their ancestral lands from exploration activities. So it is activity is not uncommon form of criminal policy by means of criminal law that gives rise to new conflicts. Therefore the criminal policy should be shifted from penal facilities to non-penal policy more accommodating community participation, so that the purpose of the criminal policy, namely the welfare of society and protect the community can be realized.Keywords: Political Criminal, Mining, Non-Penal